1998
DOI: 10.1029/97jc02441
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulations of the baroclinic dynamics of density‐driven coupled fronts and eddies on a sloping bottom

Abstract: Abstract. Numerical simulations of the baroclinic dynamics of density-driven coupled fronts and eddies are described. The simulations are based on a two-layer intermediate length scale model which filters out barotropic instability and focuses on the subinertial baroclinic evolution of density-driven flows within the context of allowing finite-amplitude height variations in the lower layer. The baroclinic destabilization of a bottom-trapped coupled front on a sloping bottom is described. In the overlying fluid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
53
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 41 publications
1
53
0
Order By: Relevance
“…A number of numerical simulations (e.g. Jiang & Garwood 1995Swaters 1998a) have also shown that the spatial structure of the baroclinic instabilities associated with density-driven flows on a sloping bottom are strongly asymmetrical in the cross-slope direction. This is in contrast to instabilities of surface-driven currents (on an f-plane), where there is no external force acting to break the underlying cross-current symmetry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of numerical simulations (e.g. Jiang & Garwood 1995Swaters 1998a) have also shown that the spatial structure of the baroclinic instabilities associated with density-driven flows on a sloping bottom are strongly asymmetrical in the cross-slope direction. This is in contrast to instabilities of surface-driven currents (on an f-plane), where there is no external force acting to break the underlying cross-current symmetry.…”
Section: Introductionmentioning
confidence: 99%
“…Swaters (1998a) described numerical simulations of the model for coupled fronts and eddies, and documented the evolution of the downslope plumes into alongslope propagating eddies. The propagation characteristics of these eddies have been studied by Swaters & Flierl (1991) and Swaters (1998b).…”
Section: Introductionmentioning
confidence: 99%
“…The result is that there is a spatial asymmetry (even on an f -plane) in the destabilization of these grounded abyssal currents. This asymmetry is clearly seen in numerical simulations (Swaters [4,8]). …”
Section: Steady Solutions Variational Principle and Stability Conditmentioning
confidence: 62%
“…For a parabolically shaped abyssal current with up slope and down slope groundings, this condition holds on the down slope flank but not on the up slope flank. This is why the instability preferentially amplifies on the down slope flank and the amplitude of the perturbations along the down slope grounding are much larger compared to those on the up slope grounding (see Swaters [4,7,8]). Physically, energy is required to move grounded abyssal fluid parcels located adjacent to the up slope grounding up the sloping bottom (against the force of gravity), while energy is released by the down slope movement of grounded abyssal fluid parcels located along the down slope grounding.…”
Section: Steady Solutions Variational Principle and Stability Conditmentioning
confidence: 99%
“…These currents form an important component in the deep "leg" of the meridional overturning circulation in the oceans. The mesoscale dynamics of these currents has been described in a series of papers [1][2][3][4][5][6][7][8][9][10][11]. All of these studies have implicitly assumed either an f or β-plane approximation in which the dynamics is modelled in a Cartesian coordinate system with the implicit assumption that the horizontal length scales are not too much larger than the internal deformation radius (on the order of about 10-100 km in the ocean).…”
Section: Introductionmentioning
confidence: 99%